Evaluasi Pelaksanaan Program Jaminan Kesehatan Nasional (JKN) dalam Upaya Meningkatkan Akses Kesehatan Masyarakat di Indonesia - Eva Nur Agustin; Jahira Fajri Madani; Kazhima Alma Azzahra; Novita Dwi Istanti (Jurnal Anestesi, 2023)
According to Law No. 36 of 2009, health is a state of health, both physically, mentally, spiritually and socially that allows everyone to lead a socially and economically productive life. To ensure this health, the government established a health insurance known as the National Health Insurance (JKN). In its implementation, the JKN program experienced several challenges and obstacles. Therefore, this study aims to evaluate the JKN program in terms of increasing public health access. The research method used was a literature review obtained from eight journals from the Google Schoolar online database between 2018 and 2023. Based on BPJS Kesehatan data as of October 2022, as many as 89.35% of the entire Indonesian population has been guaranteed health financing through the JKN program. There are several factors that affect the implementation of the JKN program, namely internal and external factors. To overcome this, various strategies are needed to optimize the JKN program in Indonesia. In addition, collaboration between stakeholders and the implementation of digitalization of health services in various health care facilities are also needed as readiness to face the global world. In its implementation, the implementation of JKN still experiences various obstacles such as low stakeholder readiness and responsiveness, facilities and infrastructure that have not been maximized, and regulations regarding the JKN program have not been available and socialized properly.